Technology migration techniques for simplified layouts with restrictive design rules - Tang, Xiaoping; Yuan, Xin (International Conference on Computer Aided Design: Proceedings of the 2006 IEEE/ACM international conference on Computer-aided design : San Jose, California; 05-09 Nov. 2006, 2006)
Designs using simple geometric layout objects (such as points, sticks and rectangles) with Restrictive Design Rules (RDRs) on each layout object (i.e., it must be placed on a set of grids subject to a set of ground rules) have been introduced as an approach to better enable design for manufacturability (DFM) in ultra-deep submicron designs[9]. In this paper, we study the problem of migrating the conventional shape-based layouts to the simplified layouts with RDR constraints. We present a migration flow which consists of two process steps: (1) conversion where shapes (such as polygons) are converted to simple geometric objects (such as sticks) while the topology is maintained, and (2) grid legalization for RDRs where the simple geometric objects are placed on grid subject to the given set of ground rules by using a novel legalization algorithm, the Minimum Perturbation-driven Graph-based Grid Legalization(MP-GGL) algorithm. We demonstrate the effectiveness of the flow by successfully migrating a set of library cells in the conventional shape-based technology to the simplified layouts with RDR constraints.